Diastereoselective synthesis of spiro[indene-2, 2′-pyrazolo[1, 2-a]pyrazoles] and spiro[indoline-3, 2′-pyrazolo[1, 2-a]pyrazoles] via 1, 3-dipolar cycloaddition. Issue 56 (24th May 2016) - Lu, Yu-Ling; Sun, Jing; Jiang, Yan-Hong; Yan, Chao-Guo
Abstract : The 1, 3-dipolar cycloaddition of cyclic azomethine imines with 2-arylideneindene-1, 3-diones in refluxing acetonitrile afforded predominately cis -1, 3-diaryl-substituted spiro[indene-2, 2′-pyrazolo[1, 2- a ]pyrazole] derivatives in good yields. Abstract : The 1, 3-dipolar cycloaddition of cyclic azomethine imines with 2-arylideneindene-1, 3-diones in refluxing acetonitrile afforded predominately cis -1, 3-diaryl-substituted spiro[indene-2, 2′-pyrazolo[1, 2- a ]pyrazole] derivatives in good yields. Significantly, the similar cycloaddition reaction of cyclic azomethine imines with 3-phenacylideneoxindoles gave polysubstituted spiro[indoline-3, 2′-pyrazolo[1, 2- a ]pyrazoles] in good yields and with high diastereoselectivity.